APOPTOSIS AND CHRONIC CARDIAC INSUFFICIENCY - A.G. Gasanov (Педиатрическая фармакология, 2009)
Research into molecular apoptosis mechanisms in patients with cardio-vascular diseases is one of the pressing issues in modern medicine. Many mechanisms of this phenomenon still remain unexamined, the role of inductors and regulators in cardiomyocyte apoptosis has not yet been fully explained. This review summarizes research data that analyze the role that various groups of cell death inductors and regulators, such as FasL, Fas-R and mitochondrial apoptosis factors. Influence of the Bcl-2 protein family as apoptosis regulators is described. Developments in programmed cell death are reviewed.Key words: apoptosis, cell death mechanisms, mitochondria, cardiamyocytes.